The challenges of E-commerce / Ahmad Fahmy Ahmad Tajudin - Ahmad Tajudin, Ahmad Fahmy (Faculty of Business and Management, 2011)
This research paper is about a study on the challenges of e-commerce. The objective of the study is to identify the most critical factors that contribute to the challenges of ecommerce. In this study, primary and secondary data will be used. This includes questionnaires, journals, books, and articles. At the end of this study, the most important factor that affects the challenges of e-commerce is mutual trust since it has the highest mean compared to other factors. The highest mean is the highest ranking while the lowest mean is the lowest ranking. It can be concluded that the ranking of the factors that affect the challenges of e-commerce are mutual trust, implementation cost and security issues.